The impact of the 50 years flood on local business at Kuala Tahan National Park, Pahang - Muhamad Zamri, Muhamad Zulwaqa' (2016)
Kuala Tahan National Park is located close to the river bank of two major rivers – Tembeling and Tahan Rivers. The area had witnessed several major floods in 1926, 1971 and as recent as 2014. Of these, the 2014 flood was the most severe has destroyed much of the infrastructure such as roads, landslides, damaged bridges, in addition to destroyed homes, property, livestock and farm produce as well. This study was aimed at investigating the impact of such traumatic event on local business in at Kuala Tahan. This study was also designed to examine the socioeconomic characteristics of local business during and after major floods of 2014. Moreover this study is to determine the relationship between acceptance local business during major flood and implication of local business after the major flood. As the result, the result shows that the mean for impact of socio-economic during and after the major flood to local business.The current devastation that has to be faced in Malaysia was the 2014 flood. The impacts left by this are mainly damages caused by the physical contact of floodwaters with materials and are therefore related to the materials which are declining physically